Physiological of Calendula Officinalis L. as Affected by Foliar Application of Nano Nitrogen and Potassium Fertilizers, Under Water Stress Conditions - Alsudani, Aqeel Abdul Abbas Abdul Zahra; Semmak, Qais Hussain Abbas Al (American Journal of Botany and Bioengineering, 2025)
An experiment was conducted in plastic pots at the nursery of the College of Agriculture/University of Kerbala during the agricultural season 2023-2023 to study the effect of foliar spraying with Nano nitrogen and potassium on some physiological traits of Calendula officinalis L. under water stress conditions. The experiment was implemented in a randomized complete block design with three replicates and three factors: the first, three concentrations of liquid Nano nitrogen (0, 2, and 4) ml L-1; the second, three concentrations of complex Nano potassium (0, 2, and 4) g L-1; and the third, two levels (50% and 100%) of the field capacity value, with the interaction between them. The averages were compared according to the least significant difference (L.S.D) at a probability level of 0.05. The results showed that spraying liquid Nano nitrogen fertilizer at a concentration of 4 ml L-1 and complex Nano potassium at a concentration of 4 g L-1 at 100% of the field capacity value significantly increased the total chlorophyll content of leaves compared to the control treatment, which gave the lowest values. The results also showed that spraying liquid Nano nitrogen fertilizer at a concentration of 0 ml L-1 and complex Nano potassium at a concentration of 0 g L-1 at 50% of the field capacity value significantly increased the content of proline and abscisic acid in leaves.